A Two-Channel Interference-Filter Photometer Digital Recording System at the AFCRL Geopole Observatory, Thule, Greenland. - Mullen,Edward G.; Lloyd,John W. F.; Davis,Daniel J. , Jr (1973)
A two-channel digital photometer system installed at the AFCRL Geopole Observatory, Thule, Greenland is described, and data from the system over the 1972 to 1973 optical observing season are presented. Results show that intensities of (OI)(lambda)5577 A can be obtained over long periods of time under varied observational conditions with high reliability. The system makes it economically feasible to study long- and short-term variations and correlations of fast time resolution optical data. (Author)